COMMENTS ON THE ARTICLE MANAGEMENT OF THE PATIENT WITH RESPIRATORY FAILURE SUFFERING FROM INFLAMMATORY DEMYELINATING POLYRADICULONEUROPATHY - I. V. Vartanova; K. N. Khrapov (Вестник анестезиологии и реаниматологии, 2017)
.